1989
DOI: 10.1080/09524622.1989.9753099
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Vocal Amplitude and Vocal Radiation Pattern in Blue Monkeys and Grey-Cheeked Mangabeys

Abstract: The substitution method was adopted from industrial acoustics (Francois and de Montussaint 1972) to "eliminate the influence of the environment" on measurements of the amplitude of vocalizations given by blue monkeys Cercopithecus mitis and grey-cheeked mangabeys Cercocebus albigena. Measurements were conducted of sound power and sound pressure level of representative utterances. Monkey vocal radiation patterns were also measured. The results showed that vocal amplitude ranged from 62 dB to 100 dB in sound pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
(9 reference statements)
0
20
1
Order By: Relevance
“…Hence, a "sound window", or a preferred frequency band for superior long-range propagation was observed. This outcome was likely due to an inversion like thermal gradient acting to alter the ray characteristics of the direction of propagation of the wave front such that rays directed toward the upper canopy are bent back toward the lower strata which are occupied by primates (Brown 1986). Appropriate gradients have been measured across tropical forest canopies, particularly in the first few hours after dawn (p.M. Waser and M.S.…”
Section: Sound Propagationmentioning
confidence: 97%
See 2 more Smart Citations
“…Hence, a "sound window", or a preferred frequency band for superior long-range propagation was observed. This outcome was likely due to an inversion like thermal gradient acting to alter the ray characteristics of the direction of propagation of the wave front such that rays directed toward the upper canopy are bent back toward the lower strata which are occupied by primates (Brown 1986). Appropriate gradients have been measured across tropical forest canopies, particularly in the first few hours after dawn (p.M. Waser and M.S.…”
Section: Sound Propagationmentioning
confidence: 97%
“…If species differences can be found in perceptual capabilities as fundamental as audiograms, it seems likely that more sophisticated aspects of audio processing will also vary in ways that reflect habitat differences. In this respect it has already been found that rain forest monkeys [blue monkeys (Cercopithecus mitis) and grey-cheeked mangabeys (Cercocebus albugena)] are significantly better at hearing their own species-specific calls in simulated forest noise than they are at detecting the calls of other species (Brown 1986). Furthermore, forest monkeys hear monkey calls in noise at much lower levels than humans are able to hear speech (Brown 1986).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Given the directional sound radiation pattern of most vertebrate vocalizations (e.g. Brown, 1989b;Brumm, 2002), we chose this array to minimize variation in sound level caused by lateral movements of the monkeys' heads. White (broad-band) noise was generated by a PC with a SB AudioPCI 128 sound card (sampling rate: 48·kHz, accuracy: 16·bit) and recorded on digital tape.…”
Section: Subjects and Apparatusmentioning
confidence: 99%
“…For example, the perception of facing angle may be of particular importance with sounds produced by biological organisms. Human listeners visually orient toward the source of speech as well as project speech toward the intended recipient of the message (Bertelson et al, 1987;Brown, 1989;Ecklund Flores and Turkewitz, 1996). Other organisms direct vocalizations such as alarm calls and territorial warnings (Fotheringham et al, 1997;Herzog and Hopf, 1984;Munn, 1986;Sherman, 1977).…”
Section: Introductionmentioning
confidence: 99%